INFLUENCE OF ENVIRONMENTAL FACTORS ON SUCCESS OF ENTREPRENEURS IN THE TRADE SUB-SECTOR IN KENYA - Karogo, Mercy Gathigia; Nyaboga, Prof. Andrew; Marwa, Prof. Mwita; Waiguchu, Prof. Muruku (European Journal of Business and Strategic Management, 2017)
Purpose: The purpose of this research was to assess environmental factors on entrepreneur success in Kenya. Methodology: The study applied a descriptive research design. The researcher used both structured questionnaire that was designed for the entrepreneurs and interview schedules that were designed for SME managers/owners. The analysis of data was done using the Statistical Package for Social Sciences (SPSS version 23.0) computer software. Results: The key findings indicate that there was a significant positive relationship between environmental factors and entrepreneurs' success apart from government support whose relationship with entrepreneurs' success is weak. Unique Contribution to Theory, Policy and Practice: The study recommended adequate government support to SMEs; improved technology; ensuring that business information is accessed by entrepreneurs as easily as possible; and developing quality physical infrastructure.